Four Years Implementation of Five-Day School: an Evaluation of Education Policy - Widiarini Widiarini; M. Zainuddin; Zulia Khoirun Nisa; Nanang Zamroji; Redhitya Wempi Ansori (Journal of Development Research, 2024)
In line with the existence of a five-day school (FDS) proposed by the Minister of Education and Culture in 2017, some cities and towns implemented this regulation, including Blitar City. In general, the purpose of this study was to evaluate the implementation of FDS in Blitar City. Specifically, the current research was aimed at investigating the achievement of fulfilling the teacher's workload in implementing the FDS, students’ character, and the level of community satisfaction after FDS implemented for 5 years. This research was conducted using a mixed method. Furthermore, the data was obtained from public and private schools at the elementary school level and junior high schools in Blitar City, students’ parents as well as. The results of this study indicate that there are 8 teachers (5,67%) teachers stated that their face-to-face meetings are less than 24 hours/week. There are 26 teachers (18,44%) who have a meeting around 24-28 hours per week. The number of teachers who have 28-32 meetings per week is 23 (16,31%) teachers. 53 (37,59%) teachers have 32-36 meetings per week. There are 31 (21,99%) teachers who have 36-40 hours of meetings per week by the provisions, character strengthening in the five-day school is implemented in curricular and co-curricular activities, students’ parents are dissatisfied with the student’s parents are dissatisfied with the implementation of the five school days. In conclusion, the policy of implementing FDS in Blitar City must be revised due to the existence of some disadvantages effect for both students and teachers.